Framing Friction: A Content Analysis Investigating How the CDC Framed Social Media Communication with the Public During the COVID-19 Pandemic - Michaela Kandzer; Valentina Castano; Lauri M Baker; Ashley McLeod-Morin (Journal of Applied Communications, 2022)
The novel coronavirus was first discovered in Wuhan, China in December 2019. This zoonotic disease quickly spread through over 100 countries, including the U.S. The World Health Organization (WHO) declared a global health emergency by the end of January 2020. Soon after, many U.S. states issued mandatory stay-at-home orders, which caused adverse effects for agricultural businesses and food supply chains. During this crisis, the Centers for Disease Control and Prevention (CDC) shared information through social media platforms such as Facebook. This study sought to understand how the CDC framed direct communication to the public about issues related to COVID-19 using Facebook videos. Five videos directly related to COVID-19 were selected from the CDC’s Facebook page for analysis. A content and framing analysis was used to determine emergent frames and the use of organization-public relationship (OPR) indicators to better understand how a public entity communicates with the public during a pandemic. Emergent frames were community, protecting yourself, encouragement to take action, understanding, and fear. A conversational tone of voice was used in four out of the five videos, and each video demonstrated the use of at least one OPR indicator. Implications from this work reinforce that Facebook videos can be used to communicate the importance of scientific information using conversational voice and OPR indicators. It is recommended that agricultural communicators include OPR indicators in social media videos during other similar zoonotic disease crises. Future research should seek to understand the public’s response to this type of scientific communication.
Keywords: zoonotic disease; strategic communication; framing; social media; public relations